Investigation of the relationship between air quality and health outcomes in Bilecik, Türkiye: A descriptive ecological study - Yücel, Mehtap; Küçükkendirci, Hasan (Scientific Reports in Medicine, 2026)
Objective: To evaluate temporal trends in air quality indicators and their ecological-level associations with respiratory and cardiovascular hospital admissions in two districts of Bilecik Province between 2020 and 2024. Methods: This ecological, retrospective study used annual district-level data from two public hospitals and two fixed air-monitoring stations in Bilecik city center and Bozüyük. Annual mean concentrations of PM₁₀, PM₂.₅, SO₂, NO₂, O₃ and CO were obtained from routine monitoring records. Hospital admissions were classified using ICD-10 codes for major respiratory and cardiovascular conditions. Descriptive trends were examined, and ecological co-variation between pollutants and total respiratory/cardiovascular admissions was assessed using Spearman’s rank correlation (p<0.05). Results: PM₁₀ levels declined in both districts, whereas PM₂.₅ concentrations increased and remained higher in Bozüyük. Respiratory and cardiovascular admissions decreased in 2020–2021 and rose again from 2022 onwards. At the district–year level, respiratory admissions were positively correlated with PM₂.₅ in Bozüyük and negatively correlated in the city center, while NO₂ showed negative correlations in both districts. Cardiovascular admissions were positively correlated with PM₂.₅ and temperature, whereas PM₁₀ showed a negative association, particularly in Bozüyük. Conclusion: Air quality indicators and hospital admissions displayed distinct temporal and spatial patterns across the two districts, with a stronger PM₂.₅ burden and clearer ecological associations in Bozüyük, the more industrialized and traffic-intense district. Although not implying individual-level causality, the findings provide policy-relevant evidence supporting prioritization of PM₂.₅-focused monitoring, emission-control measures, and integration of environmental indicators into local health-surveillance systems in medium-sized industrial regions.